17 Factors affecting implementation of home-based cardiac rehabilitation programme for patients with heart failure in four NHS sites. (21st November 2022) - Daw, Paulina; Wood, Grace ER; Veldhuijzen van Zanten, Jet JCS; Greaves, Colin J; Harrison, Alexander; Doherty, Patrick J; Dalal, Hasnain M; van Beurden, Samantha B; McDonagh, Sinead TJ; Taylor, Rod S
Abstract : Background: There is a global underutilisation of cardiac rehabilitation in heart failure. Offering alternative modes of delivery, such as home-based programmes, can lead to an increase in uptake. However, adopting this new mode of delivery may be challenging for service providers who predominantly offer centre-based programmes. Aim: The study aimed to evaluate the process of implementation in real-world clinical practice by using data generated at four NHS Beacon Sites from England and Northern Ireland which were setup to offer a novel home-based programme – the REACH-HF programme – to 200 patients. Methods: We used in-depth semi-structured interviews and an online survey. Interviews were conducted with the Beacon Site staff – these were identified using opportunity and snowball sampling. The online survey was subsequently presented to NHS staff who took part in online REACH-HF training during the COVID-19 pandemic. Normalisation Process Theory was used as a framework to guide data collection and analysis. Results: We interviewed 17 healthcare professionals working at the Beacon Sites and 17 survey responses were received (20% response rate). We identified a large number of general barriers and enablers to implementation and a smaller number of site-specific factors. The identified barriers and enablers included a lack of resources, a lack of commissioning, having interest in heart failure and working closely with the heart failure team. Different implementation contexts (urban/rural) and factors outside the healthcare team/system (quality of the REACH-HF training, the COVID-19 pandemic) were observed to negatively or positively impact the implementation process. Conclusion: The identified factors were translated into practical solutions. Following consultation with the Beacon Sites we created the REACH-HF Service Delivery Guide, which is now published on the NICE Shared Learning website. The guide is a useful tool that can be used by cardiac rehabilitation services wishing to introduce the REACH-HF programme into routine NHS practice.